Toll-like receptors (TLRs) and innate immunity - Bauer, Stefan. (Handbook of experimental pharmacology, 2008)
Overall recent research on TLRs has led to tremendous increase in our understanding of early steps in pathogen recognition and will presumably lead to potent TLR targeting therapeutics in the future. This book reviews and highlights our recent understanding on the function and ligands of TLRs as well as their role in autoimmunity, dendritic cell activation and target structures for therapeutic intervention. Toll-like receptors (TLRs) and their ligands -- Signalling of toll-like receptors -- TLR9-mediated recognition of DNA -- RNA recognition via TLR7 and TLR8 -- Fungal recognition by TLR2 and dectin-1 -- Heat shock proteins and toll-like receptors -- Nucleic acid recognition receptors in autoimmunity -- Dendritic cell subsets and toll-like receptors -- Structure of toll-like receptors -- Toll-like receptor-agonists in the treatment of skin cancer: history, current developments and future prospects -- Vaccination with messenger RNA (mRNA).